Inclusive educational management: Bibliometric analysis of research and future perspectives up to 2021 - Palomino Flores, Javier (2022)
Inclusive Educational Management (IEM) is a crucial topic in the contemporary educational sphere, focusing on ensuring that students, regardless of their abilities, cultural backgrounds, or circumstances, have access to quality education. The objective of this analysis is to provide an overview of influential research in the field of IEM, identifying patterns and gaps in the existing literature. This study conducts a bibliometric analysis of research on inclusive educational management, evaluating trends, methodologies, and areas of focus. Additionally, future perspectives in this area are projected. The results offer insight into the evolution of the field and guide researchers and professionals toward effective and sustainable inclusive practices.